Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

Which expression is equivalent to x² + 2x + 2?
(x+1-i)(x+1+i) 1
(x+1-i)(x+1-i) 2
(x + 2)(x + 1) 3
(z-1+i)(z-1--i) 4


Sagot :

Answer:

[tex](x+1-i)(x+1+i)[/tex]

Step-by-step explanation:

[tex](x+1-i)(x+1+i)\\\\=(x+1)^2 -i^2~~~~~~~~~~~~~;[a^2 -b^2 = (a+b)(a-b)]\\\\=x^2 +2x +1 -(-1)\\\\=x^2 +2x +1+1\\\\=x^2 +2x +2[/tex]